Guidelines for the Management of Student Care Systems with Digital Technology of Saraphi Technical College, Saraphi District, Chiang Mai Province - Chakkham, Apiwan; Mahavīro, Asst. Prof. Dr., Phramaha Sakun (MCU Haripunchai Review, 2025)
The objectives of this research 1.To study the current conditions of managing the student care and support system using digital technology at Saraphi Technical College, Saraphi District, Chiang Mai Province; and 2. To identify guidelines for managing the student care and support system using digital technology at Saraphi Technical College, Saraphi District, Chiang Mai Province. This qualitative research involved 25 key informants, including administrators, responsible teachers, and an experimental group. Additionally, the Delphi technique was used with 21 experts: 1) administrators from Saraphi Technical College, 2) school administrators and teachers, and 3) university instructors, all selected through purposive sampling. The research instruments were unstructured interviews and questionnaires. Data were analyzed using content analysis. The results of the research found that: 1) The current state of student care and support management revealed that student promotion and development were insufficient. There was a lack of plans or projects for promoting and developing student behavior, insufficient continuity in positive discipline promotion, no homeroom activities, and limited parental involvement in organizing activities. 2) Guidelines for managing the student care and support system using digital technology include organizing homeroom activities for students at risk, holding parent meetings, arranging life skills development programs, and providing remedial teaching tailored to student needs. Activities should emphasize developing students to be good individuals with morality, ethics, and desirable values, using creative programs that build resilience. Cloud computing should be applied for student care management, enabling parents to participate in appropriate online activities through mobile devices. Additionally, the system should include recording and summarizing activity results, storing data, and reporting outcomes to relevant stakeholders via applications.